2024
DOI: 10.3390/cells13020173
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus Receptor Expression Profiles in Human Mast Cells, Basophils, and Eosinophils

Lina Degenfeld-Schonburg,
Irina Sadovnik,
Dubravka Smiljkovic
et al.

Abstract: A major problem in SARS-CoV-2-infected patients is the massive tissue inflammation in certain target organs, including the lungs. Mast cells (MC), basophils (BA), and eosinophils (EO) are key effector cells in inflammatory processes. These cells have recently been implicated in the pathogenesis of SARS-CoV-2 infections. We explored coronavirus receptor (CoV-R) expression profiles in primary human MC, BA, and EO, and in related cell lines (HMC-1, ROSA, MCPV-1, KU812, and EOL-1). As determined using flow cytomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 76 publications
0
1
0
Order By: Relevance
“…Monocytes play a pivotal role in cytokine storm formation in COVID-19 patients, as they produce high levels of pro-inflammatory cytokines such as IL-6 and TNF-α, contributing to an exaggerated immune response to the infection. Additionally, monocytes as well as basophils and eosinophils, have been reported to express the ACE2 receptor, which is necessary for viral entry, and studies have demonstrated their susceptibility to infection [ 43 , 44 ]. This dual role of monocytes in both immune response amplification and viral susceptibility may explain the observed reduction in monocyte levels in the blood of COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Monocytes play a pivotal role in cytokine storm formation in COVID-19 patients, as they produce high levels of pro-inflammatory cytokines such as IL-6 and TNF-α, contributing to an exaggerated immune response to the infection. Additionally, monocytes as well as basophils and eosinophils, have been reported to express the ACE2 receptor, which is necessary for viral entry, and studies have demonstrated their susceptibility to infection [ 43 , 44 ]. This dual role of monocytes in both immune response amplification and viral susceptibility may explain the observed reduction in monocyte levels in the blood of COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%